2022
DOI: 10.3390/ijerph192114331
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obese Adult Patients Show Larger Benefits from Concurrent Training Compared with Pharmacological Metformin Treatment on Insulin Resistance and Fat Oxidation

Abstract: Metformin, a drug widely used to treat insulin resistance, and training that combines aerobic and strength exercise modalities (i.e., concurrent training) may improve insulin sensitivity. However, there is a paucity of clinical trials investigating the effects of concurrent training, particularly on insulin resistance and fat oxidation in overweight and obese patients. Furthermore, only a few studies have compared the effects of concurrent training with metformin treatment. Therefore, the aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Concurrent training impacts fat metabolism through various mechanisms, including an increase in the highest fat oxidation through exercise. Research by Azocar-Gallardo et al demonstrated that concurrent training led to a notable enhancement in the highest fat oxidation as compared to metformin pharmaceutical treatment (Azócar-Gallardo et al, 2022). Another approach is insulin sensitivity enhancement.…”
Section: The Fat Metabolism Mechanism In Concurrent Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrent training impacts fat metabolism through various mechanisms, including an increase in the highest fat oxidation through exercise. Research by Azocar-Gallardo et al demonstrated that concurrent training led to a notable enhancement in the highest fat oxidation as compared to metformin pharmaceutical treatment (Azócar-Gallardo et al, 2022). Another approach is insulin sensitivity enhancement.…”
Section: The Fat Metabolism Mechanism In Concurrent Trainingmentioning
confidence: 99%
“…Strength training should precede endurance training to enhance strength stimulus(Turner & Comfort, 2022). Additionally, Manage training stress to reduce progressive fatigue and strength adaptation adverse effects(Azócar-Gallardo et al, 2022). Maximise inter-session rest to minimise competing molecular signalling pathways and facilitate refuelling(Medeiros et al, 2020).…”
mentioning
confidence: 99%